Find the sum of the 17th powers of the 17 roots of the equation:
x 1 7 − 3 x + 1 = 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can also use Newton's Sum for a straightforward solution:
P 1 7 + 0 P 1 6 + 0 P 1 5 … 0 P 2 − 3 P 1 + 1 7 ( 1 ) = 0
Did the same way , nice solution sir.
Problem Loading...
Note Loading...
Set Loading...
We've x 1 7 − 3 x + 1 = 0 ⇒ x 1 7 = 3 x − 1 . . ( 1 ) Let x 1 , x 2 , x 3 , . . . , x 1 7 are roots of this equation. Putting x = x 1 , x 2 , x 3 , . . . , x 1 7 repeatedly in ( 1 ) and adding them. We get x 1 1 7 + x 2 1 7 + . . . + x 1 7 1 7 = 3 ( x 1 + x 2 + x 3 + . . . + x 1 7 ) − 1 7 By Vieta, x 1 + x 2 + x 3 + . . . + x 1 7 = 0 Hence x 1 1 7 + x 2 1 7 + . . . + x 1 7 1 7 = − 1 7